Clostridium septicum aortitis: A kiss of the devil. Issue 2 (24th December 2019) - Ranchal, Purva; Ferin, Adam; Gupta, Rahul; Malekan, Ramin; Goldberg, Joshua; Laskowski, Igor; El Khoury, Marc Y.
Abstract: Background: Clostridium septicum aortitis is a lethal infection. C. septicum has a strong association with an underlying malignancy, most commonly in the colon. Aim: Early identification methods and management strategies of C. Septicum infection. Materials and Methods: We present a 64‐year‐old man with aortic aneurysm and C. septicum bacteremia with unknown malignancy who passed away on the fourth day of hospitalization despite emergent endovascular intervention. Computed tomography showed periaortic gas which is the hallmark of infection. Discussion: This case report highlights the need of prompt surgical treatment and its different modalities along with the early use of appropriate antibiotics due to the rapid spread of infection associated with high fatality. The authors also discuss the association of C. septicum aortitis with underlying occult malignancies. Conclusion: Delay in identification and treatment of C. Septicum is associated with very high mortality rates.